2002
DOI: 10.1159/000066078
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Dysfunction in Patients with Mitochondrial Myopathy

Abstract: The present study investigates cochlear function in a group of 11 patients suffering from mitochondrial myopathy with normal or near normal audiometric pure tone thresholds, in most of whom diagnosis was histologically confirmed. A complete ENT, neurologic and audiological work-up, including transiently evoked otoacoustic emissions, was performed in all patients in order to estimate cochlear function. Compared to control subjects, most patients had absent otoacoustic emissions (OAE) in spite of normal hearing,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Moreover, in some cases a central dysfunction has been reported (Chinnery et al 2000;Korres et al 2002). Sue et al (1998), in a clinical study demonstrated a cochlear lesion in all the 18 MELAS patients with hearing loss reported in their study (Sue et al 1998).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Moreover, in some cases a central dysfunction has been reported (Chinnery et al 2000;Korres et al 2002). Sue et al (1998), in a clinical study demonstrated a cochlear lesion in all the 18 MELAS patients with hearing loss reported in their study (Sue et al 1998).…”
Section: Discussionmentioning
confidence: 78%
“…The stria vascularis shows a high level of metabolic activity, abundant Na+ and K+-ATPase pumps that use ATP to maintain endolymphatic homeostasis of the ions (Chinnery et al 2000;Korres et al 2002), moreover stria vascularis cells have a low reproduction rate (Chinnery et al 2000). Outer hair cells, responsible for amplification of the local sound stimuli are highly metabolically active and do not duplicate (Chinnery et al 2000;Korres et al 2002). Inner hair cells and their afferent nerves also require large amounts of energy and do not duplicate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Decreased amplitude of emissions in the presence of normal audiometric thresholds may indicate an underlying cochlear pathology that may result in a clinically signi cant hearing impairment in the future. 15 According to these, otoacoustic emissions have been used to detect cochlear dysfunction caused by ototoxic drugs 8 and in monitoring hearing loss associated with long-term exposure to intense noise, prior to any change in pure-tone audiometric thresholds. 9 The most clinically useful method of recording DP is a DP-gram, in which amplitude is considered a function of f2 frequency at xed stimuli levels.…”
Section: Discussionmentioning
confidence: 99%
“…Both syndromic and non-syndromic SNHL are frequently associated with mitochondrial dysfunction, because the stria vascularis has high energy requirements combined with a low regeneration rate. Moreover, the hair cells are unable to replicate and have great energy demands [89,90] . Mitochondrial mutations include large rearrangements as well as mutations limited to a few base pairs.…”
Section: Mitochondrial Non-syndromic Hearing Lossmentioning
confidence: 99%